2018
DOI: 10.1016/j.echo.2018.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of Three-Dimensional Echocardiographic Regional Myocardial Strain with Cardiac Computed Tomography for Noninvasive Evaluation of the Hemodynamic Impact of Coronary Stenosis in Patients with Chest Pain

Abstract: Background Combined evaluation of coronary stenosis and the extent of ischemia is essential in patients with chest pain. Intermediate-grade stenosis on computed tomographic coronary angiography (CTCA) frequently triggers downstream nuclear stress testing. Alternative approaches without stress and/or radiation may have important implications. Myocardial strain measured from echocardiographic images can be used to detect subclinical dysfunction. The authors recently tested the feasibility of fusion of three-dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 66 publications
(43 reference statements)
0
16
0
Order By: Relevance
“…Alternative approaches have been explored to enhance the ability of resting echocardiography to identify patients with CAD. Mor-Avi et al 11 tested the feasibility of fusing resting three-dimensional echocardiography-derived regional LV longitudinal strain with coronary arteries from cardiac computed tomography. This allowed assessment of the hemodynamic significance of coronary stenosis in patients with chest pain without performing stress testing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternative approaches have been explored to enhance the ability of resting echocardiography to identify patients with CAD. Mor-Avi et al 11 tested the feasibility of fusing resting three-dimensional echocardiography-derived regional LV longitudinal strain with coronary arteries from cardiac computed tomography. This allowed assessment of the hemodynamic significance of coronary stenosis in patients with chest pain without performing stress testing.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Myocardial deformation imaging using two-dimensional (2D) speckle-tracking echocardiography (STE) is a valuable tool, providing comprehensive quantitative assessment of myocardial function beyond EF and qualitative assessment of RWMAs. [6][7][8][9][10][11] Previous studies have shown that peak systolic longitudinal strain is reduced in patients with significant CAD, even when resting LV wall motion and EF are preserved. 2 However, one of the main limitations of STE is load dependency, which can affect the diagnostic accuracy of myocardial function evaluation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent developments in fusion technology have enabled physicians to perform hybrid anatomo-functional imaging with stress echocardiography or similar echocardiographic techniques and CTA. [32][33][34] Unfortunately, no study has yet reported on the incremental comparative accuracy of such hybrid imaging in comparison to invasive assessments, even if reports using CT-FFR as gold standard are already available. 35 Cardiac magnetic resonance has gained significant ground in the comprehensive anatomic and functional assessment of cardiovascular disease.…”
Section: Hybrid Imagingmentioning
confidence: 99%
“…Global longitudinal strain has emerged as a dependable metric to support clinical decision-making, although it is limited by the fact that it is a unidirectional, generalized measure of function. The added ability to reliably measure regional strains in all cardiac strain directions is advantageous, especially in the evaluation of ischemic heart disease with regional dysfunction [4][5][6].…”
Section: Introductionmentioning
confidence: 99%